Historia Morbi of the Hero of A.P. Chekhov's Short Story The Black Monk: Textual and Intertextual Forms of its Presentation - Kubasov, Aleksandr (Slavica, 2023)
The ambiguity of the presentation of the illness of the protagonist of Chekhov’s short story The Black Monk and the author's attitude to it is discussed in this paper. The essential role of irony in the story is noted, due to the historical and literary context and the intertext that arises on its basis. The ironic modality is induced, on the one hand, due to the connection of the story with the early work of the writer, and on the other hand, with the works of other authors. The role of Griboyedov's comedy Woe from Wit as a catalyst for irony is also discussed. The ironic modality does not exclude the formulation of a serious problem of the inauthentic existence of humans but gives it an ambivalent character. The interweaving of the conditional beginning and the unconditional in the depiction of the hero and his illness allows Chekhov to pose the ontological problem of the inadequacy of the self-esteem of the individual.